Behind the Therapeutic Effects of Royal Jelly: Recent Advances in the Specific Properties of 10-Hydroxydecanoic Acid - Carla Gasbarri; Guido Angelini (Molecules, 2025)
Since ancient times, Royal Jelly (RJ) has been known for its remarkable properties in traditional medicine, and it is still widely recommended for mental and physical well-being. RJ consists of a unique and complex mixture of multiple constituents in different concentrations, and some of its biological activities are directly associated with specific components not found elsewhere in nature, such as (E)-10-hydroxy-2-decenoic acid (10-HDA) and its precursor 10-hydroxydecanoic acid (10-HDAA), two medium-chain fatty acids. Together, 10-HAD and 10-HDAA represent the major constituents of the total lipid fraction in RJ, but despite their structural similarity, the former has been extensively investigated over the years, while the latter has been only marginally reported. This review focuses on the promising effects of 10-HDAA that have emerged in a series of recent in vitro, in vivo, and docking simulation studies. Important bioactivities were observed for 10-HDAA, tested both as an individual compound, especially for immunoregulatory, estrogenic, and anti-inflammatory activities, and in synergic combination with other molecules. Specific anti-infective effects against endemic diseases, as well as the structural modification to synthesize biocompatible and biodegradable 10-HDAA-based amphiphiles, are also reported.